Treatment Success and User-Friendliness of An Electric Toothbrush App: A Pilot Study - Viviane Humm; Daniel Wiedemeier; Thomas Attin; Patrick Schmidlin; Stefanie Gartenmann (MDPI AG, 2020)
Electronic and mobile health (eHealth/mHealth) are rapidly growing areas in medicine and digital technologies are gaining importance. In dentistry, digitalization is also an emerging topic, whereby more and more applications are being offered. As an example, using real-time feedback, digital application software (an app) was designed to help users brush their teeth more accurately. However, there is no data on the effectiveness and haptic of such apps. Therefore, a single-blinded, randomized controlled clinical trial was designed: twenty volunteers received an electric toothbrush with an associated app to assess whether the app-assisted toothbrushing is better than without. After a short period of familiarization with the electric toothbrush, plaque index (O'Leary et al. 1972) was recorded and subjects were assigned to the test (with app; n = 10) or the control group (no app; n = 10). At the end of the 2-week pilot study period, plaque was again assessed and participants in the test group completed a questionnaire about the app's user-friendliness. Statistical analysis revealed no significant differences between the test and control groups. The plaque index improved on average by 8.5% points in the test and 4.7% points in the control group. Fifty percent of the test group participants were of the opinion that they had achieved better cleaning results and would recommend the app to others, although the app contributed only marginally to increased plaque removal. However, such apps may nevertheless be helpful as motivational tools, especially when tracking and monitoring cleaning data. Therefore, more development and research on this topic is indicated.